FAKTOR-FAKTOR YANG MEMPENGARUHI STUKTUR MODAL (Study Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada tahun 2013-2015) - Desi Yuni Pratiwi, 13.05.52.0064; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2017)
This study aims to determining the effect of company size, liquidity, profitability, business risk and asset structure on capital structure at manufacture company listed in Indonesian Stock Exchange 2013-2015. In this study popuation are used companies registered in Manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2013-2015 . The sampling technique using purposive sampling. Mechanical testing data is to use a multipe linear regression analysis. The results of this study show that company size significant positive correlation to capital structure, Liquidity and profitability significant negative correlation to capital structure. While business risk and asset structure had no significant effect on the capital structure. Key word : Company Size, Liquidity, Profitability, Business Risk, Asset Stucture and Capital Stucture.Keywords: Company Size, Liquidity, Profitability, Business Risk, Asset Stucture and Capital Stucture